(untitled) (Veterinary Science, 2017)
The impaction of the colon and ileum occupy a large percentage of the casuistry of equine colic. Its resolution depends on the integrity of the gastrocolic reflex essential to keep hydrated content and motility. At present there is no clinical protocol an evaluation. The overall objective of this project, based on existing knowledge, was to make a standard for semiological and ultrasonographic study of the integrity of the gastrocolic reflex and anatomophysiology the stomach, small intestine, ileocecal valve, cecum and colon. The experiment was conducted on 10 healthy adult horses. We used an ultrasound Medison, Mysono model with a 5 MHz convex transducer and a DP50 Mindray Ultrasound, micro convex transducer of 5 to 8.5 MHz, using transcutaneous technique, in order to evaluate the transit from the stomach into the intestine and the influence it has faster gastric filling on colonic motility through the gastrocolic reflex. Ultrasound diagnosis supplemented in real time, in terms of echotexture, measurement and evaluation of peristalsis. The reflection is caused by the provision of early enteralfluids via nasogastric tube. The different fluid formulation was made for the purpose of assessing the degree of improvement of the ultrasound image, allowing accurate data from intestinal functionality, standardizing the clinical procedure.